Demand, distribution, productivity, structural change, and (secular?) stagnation - Michalis Nikiforos (Levy Economics Institute of Bard College, 2020)
The present paper emphasizes the role of demand, income distribution, endogenous productivity reactions, and other structural changes in the slowdown of the growth rate of output and productivity that has been observed in the United States over the last four decades. In particular, it is explained that weak net export demand, fiscal conservatism, and the increase in income inequality have put downward pressure on demand. Up until the crisis, this pressure was partially compensated for through debt-financed expenditure on behalf of the private sector, especially middle- and lower-income households. This debt overhang is now another obstacle in the way of demand recovery. In turn, as emphasized by the Kaldor-Verdoorn law and the induced technical change approach, the decrease in demand and the stagnation of wages can lead to an endogenous slowdown in productivity growth. Moreover, it is argued that the increasingly oligopolistic and financialized structure of the US economy also contributes to the slowdown. Finally, the paper argues that there is nothing secular about the current stagnation; addressing the aforementioned factors can allow for growth to resume, as has happened in the past.
Keywords: E02; E11; E12; E21; E22; E32; O33; 330; Stagnation; Demand; Distribution; Technical Change; Institutions